Quantifying bias and uncertainty in historical data collections with probabilistic programming - Leo Lahti; Eetu Mäkelä; Mikko Tolonen (Germany, 2022)
The enhanced access to ever-expanding digital data collections and open computational methods have led to the emergence of new research lines within the humanities and social sciences, bringing in new quantitative evidence and insights. Any data interpretation depends critically on understanding of the scope and limitations in data collection, as well as on reliable downstream analysis. Quantitative analysis can complement qualitative research by providing access to overlooked information that is accessible only through systematic discovery and analysis of latent patterns underlying the available data collections. Probabilistic programming is an expanding paradigm in machine learning that provides new statistical tools for intuitive interpretation of complex data sets. This new paradigm stems from Bayesian analysis and emphasizes explicit modeling of the data generating processes and associated uncertainties. Despite its remarkable application potential, probabilistic programming has so far received little attention in computational humanities. We use a brief case study in computational history to demonstrate how probabilistic programming can be incorporated in reproducible data science workflows in order to detect and quantify bias in a widely studied historical text collection, the Eighteenth Century Collections Online.
1st Workshop on Computational Humanities Research